Image of Ideal Housewife in Yoga Arizona's HappyFresh #BikinMertuaHappy Advertisement - Saptaningsih, Nur; Sofian, Ela Sofiarti; Sumarlam, Sumarlam (Jurnal Lingua Idea, 2023)
Advertisement has the potential to exploit female figures elaborated with particular signs or language that allude to gender bias in society to achieve commercial goals. One of the representations of women in advertisements shows the social position of women as subordinated figures in the domestic areas. This strategy is also applied in Yoga Arizona’s Happyfresh #BikinMertuaHappy advertisement posted on his Instagram account on July 25, 2020. This study examined the image of the ideal housewife as depicted in that advertisement. The research data include the visual and textual elements sourced from the video and caption in the advertisement. The depiction of the ideal housewife was analyzed using the Critical Discourse Analysis approach by Sara Mills (2003), examining the subject-object and writer-audience positions. This study has identified that the housewife plays double roles as the subject and the object in the advertisement, and the writer positions the audience as those who share common characteristics with the main character. This study has revealed that the ideal housewife depicted is the one that is capable, attentive, and reliable in taking care of the family to meet the mother-in-law’s standards. The positioning of women in the advertisement supports the gender imbalance in a domestic context.